Molecular Analysis of Genetic Elements Responsible for XDR in Highly Successful Pathogen Acinetobacter Baumannii Isolated from Clinical Samples of Iraqi Patients - Rawa Abdul Redha Aziz (Journal of Global Pharma Technology, 2017)
Objective(s): A. baumannii infections have gained attention due to the high number of infected soldiers serving in Iraq and Afghanistan. Current study focus on the phenotypic and genotypic detection of antibiotic resistant genes among Iraqi A. baumannii isolates to classify them into appropriate antibiotic resistant level.Material and methods: Antibiotic resistant genes were screened among 24 A. baumannii isolates collected from Baghdad and Al- Najaf hospitals using different phenotypic methods. Genotypic detection was done using PCR. Results: All isolates showed positive results to recA gene at 425bp. Antimicrobial susceptibility testing revealed 100% resistance towards Ceftazidime, Amoxicillin-clavulanic acid, Ticarcillin-clavulanic acid, and Cefepime. Also, 50% isolates were resistant to Colistin sulphate, while 66.7% isolates were resistant to tigecycline. The MIC test for polymyxin B revealed that 83.3% isolates were resistant to ˃32µg/ml. Results showed 16.7% of A. baumannii isolates was MDR, 70.8% was XDR, and 12.5% of isolates was PDR. Also, 87.5% of isolates were carbapenemase producers; while 33.3% were ESBLs producers. PCR studies showed among 22 antibiotic resistant genes tested, there was 100% and 70.8% for aac(6)-Ib, ant(4)IIb-, and aac(3)-I, respectively. Also, 13% of the isolates were harbored mexX gene. Results showed 50% had rmtD followed by rmtA and rmtF 45.83%. Some of the isolates encode ParC2 and GyrA2 (75% and 91.67%, respectively). The OXA 23 and OXA 51 were detected among 29.17% and 75%, respectively. Conclusion: Current study found most A. baumannii isolates were MDR, XDR, and even PDR pathogens among wound infected patients in Baghdad and Al-Najaf hospitals.Keywards: ESBLs, Modified Hodge test, carbapenemase, Pan drug resistant (PDR), multiple resistant (MDR), extremely resistant (XDR).